Tunisia's development perspectives - Hilmar Kaht (Intereconomics, 1973)
Tunisia is at the beginning of the second decade of its development planning. The first decade (1961–1972) was put under the heading of Socialism. The influence of the socialist conception on development planning was reflected by a high share of public investments in total investments as well as intensified furthering of agricultural cooperatives.
Keywords: 330; Tunisia